Detection of lymph node metastases in patients with prostate cancer: Comparing conventional and digital [18F]‐fluorocholine PET‐CT using histopathology as a reference. (8th August 2022) - Bjöersdorff, Mimmi; Puterman, Christopher; Oddstig, Jenny; Amidi, Jennifer; Zackrisson, Sophia; Kjölhede, Henrik; Bjartell, Anders; Wollmer, Per; Trägårdh, Elin
Abstract: Background: Positron emission tomography‐computed tomography (PET‐CT) with [ 18 F]‐fluorocholine (FCH) is used to detect and stage metastatic lymph nodes in patients with prostate cancer. Improvements to hardware and software have recently been made. We compared the capability of detecting regional lymph node metastases using conventional and digital silicon photomultiplier (SiPM)‐based PET‐CT technology for FCH. Extended pelvic lymph node dissection (ePLND) histopathology was used as a reference method. Methods: The study retrospectively examined 177 patients with intermediate or high‐risk prostate cancer who had undergone staging with FCH PET‐CT before ePLND. Images were obtained with either the conventional Philips Gemini PET‐CT ( n  = 93) or the digital SiPM‐based GE Discovery MI PET‐CT ( n  = 84) and compared. Results: Images that were obtained using the Philips Gemini PET‐CT system showed 19 patients (20%) with suspected lymph node metastases, whereas the GE Discovery MI PET‐CT revealed 36 such patients (43%). The sensitivity, specificity, and positive and negative predictive values were 0.3, 0.84, 0.47, and 0.72 for the Philips Gemini, while they were 0.58, 0.62, 0.31, and 0.83 for the GE Discovery MI, respectively. The areas under the curves in a receiver operating characteristic curve analysis were similar between the two PET‐CT systems (0.57 for Philips Gemini and 0.58 for GE Discovery MI, p  = 0.89). Conclusions: Marked differences in sensitivity and specificity were found for the different PET‐CT systems, although the overall diagnostic performance was similar. These differences are probably due to differences in both hardware and software, including reconstruction algorithms, and should be considered when new technology is introduced.